Medieval hagiographic sources and Medical Anthropology. Thaumaturgic saintliness as a cultural device in the defence of health in 12th-14th centuries Orvieto - Enrico Petrangeli (AM. Rivista della Società Italiana di Antropologia Medica, 2002)
Medieval hagiographic sources and Medical Anthropology.Thaumaturgic saintliness as a cultural device in the defence of health in 12th-14th centuries Orvieto